Mobilizing sprint trainings in precompetitive training periods in swimming sport - Grigoriev, V. I.; Davydova, O. S.; Oshev, A. A. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to improve the efficiency of the precompetitive training of swimmers of the university sports perfection group by increasing the number of sprint exercises against the less hours of swimming practices.